The present status of insecticide resistance - Busvine, J. R. (1963)
The author first considers the concepts of “behaviouristic resistance” and “vigour tolerance”. He concludes that neither phenomenon, if it exists at all, is likely to present a serious obstacle to major insect control schemes. On the other hand, physiological resistance is a real and important problem and the number of resistant species is growing at an alarming rate. However, since resistance is often localized and usually confined to one or a few insecticides, the full impact has not yet been felt. This situation is likely to change and resistance may eventually become sufficiently general to jeopardize the success of campaigns to eradicate malaria and other vector-borne diseases. The author discusses the various countermeasures that have been adopted on the recommendation of the WHO Expert Committee on Insecticides and adds some suggestions of his own for future research and for the application of insecticides in ways calculated to prevent or overcome resistance.